Discussões em torno à formação do professor de arte - Siqueira, Ana Cristina dos Santos (2010)
This dissertation aims to develop study on initial teacher of Art and on the design of teaching art in the XX and XXI, in education. Seeks to verify the process and rules of discipline and training of teachers, which compartmentalize the content in Visual Arts, Music, Dance and Theatre, and increasingly concerned with the specialization of language and not with the formation of the conception of art. For this methodological procedure is to document analysis and is structured as follows: Chapter I presents a brief history about the teaching of art in Brazil. Chapter II deals with the rules of discipline and training courses for teachers of Art. Chapter III deals with the philosophical influences of the teaching of art and its onset in the classroom, in public schools in São Paulo; curriculum proposals that impacted official documents in the public schools in São Paulo, are in it are considered. Chapter IV emerges from reflection on teacher training, converging to the design of the teaching of contemporary art. Theoretical parameters considered were to: Ana Mae Barbosa (1985), (1998), (2002), Mirian Celeste Martins (2007), LDB 5692 (1971), LDBEN 9395 (1996), NCP (2001), SEE / CENP / FDE (2006), SEE / CENP / FDE (2008), Lisbon and Kerr (2005), MEC / SESu (1999) Alfredo Bosi (2000), CNE / CP (2001), Deleuze and Guattari. Part of the documents regulating the teaching of Art and the training of teachers in public schools in São Paulo. Thus allowing inferences and conclusions about what was said